The Impact of Motivation and Environment on Employee Performance with Organizational Commitment as Intervening Variable - Adelfigita Frastika; Rosaly Franksiska (International Journal of Social Science and Business, 2021)
Employee performance is the result achieved by the employee in completing the work assigned by the company to the employee. The inconsistencies of previous research and also overlooking the chance that organizational commitment may act as intervening variable is the problem that this research highlight. The purpose of the study was to test the effect of work motivation and work environment on employee performance with organizational commitment as an intervening variable. This type of research is causal-quantitative research. Saturation sampling was used in this research.  110 employees of PT Abioso Batara Alba, Boyolali Regency, as the sample. Data collection techniques in this study using a questionnaire. The hypothesis testing technique is in the form of path analysis using SPSS version 20 and the Sobel test. The results showed that work motivation had an effect on employee performance. Organizational commitment does not mediate the effect of work motivation on employee performance. Good work motivation will increase employee performance. The work environment has an effect on employee performance. Organizational commitment does not mediate the effect of the work environment on employee performance. Employee performance will improve if they are motivated at work. Employees do not need to be devoted to the firm to increase performance because the company's good work motivation will directly improve employee performance. Employees do not need to be dedicated to the company first in order for the construction of a nice work environment to have a direct impact on employee performance.